MODELING OF PLANT TISSUE GROWTH AND DEVELOPMENT WITH L-SYSTEMS - U. S. Zubairova; A. V. Penenko; S. V. Nikolaev (Вавиловский журнал генетики и селекции)
An introduction to modeling of dynamical systems possessing dynamical structures with L-systems is given. Application of L systems is illustrated by models of plant tissue growth and control of state variable distribution in the growing tissue.